New Therapies for Obstructive Sleep Apnea - White, David P. (Seminars in Respiratory and Critical Care Medicine, 2014)
A strong demand for new obstructive sleep apnea (OSA) therapies exists and several are emerging. Hypoglossal nerve stimulation is designed to activate upper airway muscles. The initial study from Inspire (Maple Grove, MN) suggests that the device will work well in a very selective group of OSA patients. However, it is likely to be quite expensive. The Winx device (ApniCure, Redwood City, CA) works by establishing a vacuum in the oral cavity, which pulls the uvula and soft palate forward and stabilizes the tongue position. The current device works in approximately 40% of patients and the early data suggest adherence may be quite good. The Provent device( Theravent, San Jose, CA) has been available for several years and is disposable. It is to be attached to the nares nightly and establishes substantial expiratory resistance. Multiple studies suggest that Provent can successfully treat OSA in about 35 to 50% of the patients. However, acceptance and adherence may be a problem. OSA phenotyping is not a therapy, but a way to determine exactly what causes airway collapse in each patient, which can vary substantially. This may allow for individualization of apnea therapy. New methods to prevent supine sleep and surgically implantable devices to treat OSA are also evolving.
Keywords: sleep apnea; hypoglossal nerve; Winx; Provent; phenotyping